2011
DOI: 10.1348/000712610x524291
|View full text |Cite
|
Sign up to set email alerts
|

Differences in eye-movement patterns between anorexic and control observers when judging body size and attractiveness

Abstract: Attentional biases may influence the eye-movements made when judging bodies and so alter the visual information sampled when making a judgment. This may lead to an overestimation of body size. We measured the eye-movements made by 16 anorexic observers and 16 age-matched controls when judging body size and attractiveness. We combined behavioural data with a novel eye-movement analysis technique that allowed us to apply spatial statistical techniques to make fine spatial discriminations in the pattern of eye-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 46 publications
4
37
2
Order By: Relevance
“…However, the comparison between rAN and CN(OVER) was not ( t  = 0.94, p  > 0.05). These results suggest that accurate body size estimation took approximately 1 to 2 fixations less than inaccurate estimation, and critically, that participants appeared to make their decisions after ∼2 to 2.5 s. Consistent with George et al,13 this therefore justified restricting the eye movement analysis to the first 2,000 ms following stimulus onset.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…However, the comparison between rAN and CN(OVER) was not ( t  = 0.94, p  > 0.05). These results suggest that accurate body size estimation took approximately 1 to 2 fixations less than inaccurate estimation, and critically, that participants appeared to make their decisions after ∼2 to 2.5 s. Consistent with George et al,13 this therefore justified restricting the eye movement analysis to the first 2,000 ms following stimulus onset.…”
Section: Resultssupporting
confidence: 82%
“…In earlier work13 using this analysis method, we showed that the distribution of fixation durations in each cell of the sampling grid is rarely normal, but that the correlation between fixation duration and fixation count is very high (typically r  > 0.9). Therefore, as before, we chose fixation counts per cell (also known as fixation density) as our outcome variable.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations